2006
DOI: 10.1038/sj.ki.5001899
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonates prevent experimental vascular calcification: Treat the bone to cure the vessels?

Abstract: Bisphosphonates are inhibitors of bone resorption that are widely used to treat osteoporosis. Price and colleagues demonstrate that ibandronate suppressed the development of uremia-related vascular calcification in rats. These findings extend the link between bone remodeling and vascular calcification to the context of chronic renal failure, opening perspectives toward novel therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 16 publications
1
30
0
1
Order By: Relevance
“…[1][2][3][4] Because the presence of vascular calcification is strongly associated with increased cardiovascular morbidity and mortality, several studies in both animals and humans have sought ways to reduce the extent of vascular calcification. [5][6][7][8][9][10] However, satisfactory therapies have not yet been established. 11 Adenine-induced renal failure is one of the commonly used animal models for studying the development of vascular calcification, but the prevalence of vascular calcification in this model is not very high.…”
mentioning
confidence: 99%
“…[1][2][3][4] Because the presence of vascular calcification is strongly associated with increased cardiovascular morbidity and mortality, several studies in both animals and humans have sought ways to reduce the extent of vascular calcification. [5][6][7][8][9][10] However, satisfactory therapies have not yet been established. 11 Adenine-induced renal failure is one of the commonly used animal models for studying the development of vascular calcification, but the prevalence of vascular calcification in this model is not very high.…”
mentioning
confidence: 99%
“…Cbfa-1 and OPN have previously been described as markers of VSMC transition to osteoblast-like cells. BPs have been widely used in the treatment of excessive bone resorption, hypercalcemia and osteoporosis (12,13). Etidronate has been reported to decrease the intima-media thickening of carotid arteries (20).…”
Section: Discussionmentioning
confidence: 99%
“…The classical pharmacological effects of BPs appear to result from two key properties: their affinity for bone mineral and their inhibitory effects on osteoclasts. Mineral binding affinities differ among the clinically used BPs, and this may influence their differential distribution within bone, their biological potency and their duration of action (12,13). It is reported that ibandronate prevents experimentally induced arterial calcification in uremic rats (14).…”
Section: Introductionmentioning
confidence: 99%
“…Previous experimental animal studies have demonstrated that bisphosphonates, especially when given in higher doses, can induce osteomalacia (124) or result in accumulated microdamage (125,126). In the later stages of CKD a potential problem of bisphosphonate therapy is diminished bone remodeling that could lead to reduced repair of microcracks and impairment of bone strength (108). The frequency of microcracks in clinical studies of patients on long-term bisphosphonates varies from low (127) to high, with an increased accumulation of microdamage (128), although there is as yet no clinical evidence demonstrating that bisphosphonates actually result in impairment of bone strength.…”
Section: Accumulation Of Bisphosphonates and Low Bone Turnover In Ckdmentioning
confidence: 99%
“…It may be by inhibition of bone resorption, with reduced efflux of calcium and phosphate limiting their availability for deposition in the vasculature (108) or their ability to influence the activity of the VSMC NaPi co-transporter. Alternatively, bisphosphonates may have direct effects on the vessel wall and, like pyrophosphate, on crystal formation.…”
Section: Bisphosphonates and Vascular Calcificationmentioning
confidence: 99%